Characterization and optimization of aluminum nitride, poly silicon/thick silicon oxide and inter-facial investigation of Al-Ge eutectic bond - Kugatharshine, Selvaratnam (2015)
This project mainly documents the theory, experimental results and analysis of local stress and full map stress measurement of Aluminum Nitride film using SEMDEX A21, investigation of interface of Al-Ge Eutectic bond and startup and evaluation of Filmetrics (F64-c). Residual stress is a critical issue in thin film technology. With stressed film, defects such as dislocations, voids, and cracking may occur. Therefore local stress and full map stress measurement is essential to identify the issues related to the stress non-uniformity. This report explains the basic theory behind the stress induction and the working principle of the machinery used in the measurements, such as SEMDEX A21. Method of stress calculation in the various directions like, stress-x, stress-y, stress-45⁰, stress-135⁰, difference in stress x and y and, difference in stress 45⁰ and 135⁰ are clearly explained. Four templates were created to perform the stress calculation in various directions with step sizes of 0.7mm and 3.6mm in Macro Excel (VBA). Using the details obtained from full map stress distribution map, yield enhancement for tensile and compressive AlN film was done. Details of the experiment and the analysis carried out to investigate the interface of eutectic bond (Al -Ge) are mentioned in this report. Cross-Sectional Transmission Electron Microscopy (XTEM) and Energy-dispersive X-ray spectroscopy (EDX) analysis are done to check the cross section of interface and elements presence at the interface. Bonding conditions are also mentioned with the use of phase diagram. New metrology tool which is Filmetrics 64-c is capable of measuring the thickness of single and multi-films. To ensure the reliability of this tool, it’s matched with opti-probe which is also a thickness measurement machine. Reliability experiment details of single layer and multi-layers are explained in this article.